Development of IoT Indirect BOD Monitoring System Based on Electronic Nose Technology - Satetha Siyang (2019)
© 2018 IEEE. Smell is a good indicator of water quality. In this work, we develop the IoT smelling device to estimate BOD value of wastewater based on electronic nose technology. The BOD monitoring device consist of four important modules as follow: (1) sensor module, (2) power module, (3) microprocessor (MPU) module and (4) GSM/GPRS module. The system was designed for ease of use and easy to installation in the remote field area. The indirect BOD measurement by using electronic nose was studied to develop mathematical model for the device's firmware. The result show that e-nose technology can be used to estimate the BOD value of wastewater with R-square value is 0.8817. It need more experimental detail, as to quantify the sensor signal and calibrate its value to BOD, thereby opening the opportunity for IoT indirect BOD measurement monitoring based on e-nose technology to compete conventional BOD evaluation techniques in the future.